Étale Fundamental Groups of Strongly F-Regular Schemes. (30th October 2017) - Bhatt, Bhargav; Carvajal-Rojas, Javier; Graf, Patrick; Schwede, Karl; Tucker, Kevin
Abstract: We prove that a strongly F -regular scheme X admits a finite, generically Galois, and étale-in-codimension-one cover X → X such that the étale fundamental groups of X and X_reg agree. Equivalently, every finite étale cover of X_reg extends to a finite étale cover of X . This is analogous to a result for complex klt varieties by Greb, Kebekus, and Peternell.